2003
DOI: 10.2337/diacare.26.8.2378
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygenation Accelerates the Healing Rate of Nonischemic Chronic Diabetic Foot Ulcers

Abstract: OBJECTIVE -To study the effect of systemic hyperbaric oxygenation (HBO) therapy on the healing course of nonischemic chronic diabetic foot ulcers. RESEARCH DESIGN AND METHODS-From 1999 to 2000, 28 patients (average age 60.2 Ϯ 9.7 years, diabetes duration 18.2 Ϯ 6.6 years), of whom 87% had type 2 diabetes, demonstrating chronic Wagner grades I-III foot ulcers without clinical symptoms of arteriopathy, were studied. They were randomized to undergo HBO because their ulcers did not improve over 3 months of full st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
248
1
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(263 citation statements)
references
References 14 publications
3
248
1
9
Order By: Relevance
“…These results are in contrast to several cohort (7,(26)(27)(28)) and open-label randomized trials (5,6,8,9) where no sham placebo was used. The study by Duzgun et al (8), one of the largest trials published, often is quoted as the justification for HBOT utility in treating diabetic wounds (29).…”
Section: Adverse Eventscontrasting
confidence: 87%
See 1 more Smart Citation
“…These results are in contrast to several cohort (7,(26)(27)(28)) and open-label randomized trials (5,6,8,9) where no sham placebo was used. The study by Duzgun et al (8), one of the largest trials published, often is quoted as the justification for HBOT utility in treating diabetic wounds (29).…”
Section: Adverse Eventscontrasting
confidence: 87%
“…Defining the most effective treatment strategies is essential to reducing the burden of this disease (1). Hyperbaric oxygen therapy (HBOT) has been used as an adjuvant treatment for difficult-to-heal chronic diabetic foot wounds; however, most evidence for its efficacy is based on observational cohort studies or open-label randomized trials (5)(6)(7)(8)(9). HBOT requires significant patient time and financial commitment compared with conventional wound care without HBOT.…”
mentioning
confidence: 99%
“…Wound healing hyperbaric protocols involve daily treatments of 1.5 to 2 h for 20 to 40 days. Kessler et al in their randomized control study on hyperbaric oxygen therapy to heal nonischemic diabetic foot ulcers concluded that this hyperbaric oxygen therapy helps in wound healing by promoting neovascularisation, recruitment of stem cells, production of growth factors, and improved cell migration [1].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperbaric oxygen therapy has been used for the healing of diabetic ulcers, chronic wounds, and post traumatic wounds [1]. As compared with hyperbaric oxygen therapy, several studies have been conducted in assessing the effectiveness of topical oxygen therapy [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Kalani et al proved HBOT to be more effective compared with traditional treatment in patients with diabetic foot ulcers (respectively, 76% vs. 48% of completely healed patients) [8]. Despite very high short-term improvement resulting from HBOT intervention in patients with neuropathic ulcers, the aforementioned improvement may disappear at the 2-week follow-up [9]. Similar positive results in HBOTbased therapy of non-healing ulcers were reported by Kaur et al [10].…”
Section: Discussionmentioning
confidence: 58%